Encyclopedia of condensed matter physics - Bassani, G. F. (Giuseppe Franco), 1929-; Liedl, G. L. (Gerald L.); Wyder, Peter, 1934- (Gale virtual reference library, 2005)
Covers the fundamental theoretical aspects of condensed matter physics. Includes theoretical aspects of quantum mechanics, mechanics, electrodynamics, relativity, statistical mechanics, and elementary particles that form the core physics background for the field.